Pengembangan Kompetensi Pegawai pada Kantor Kecamatan Ilir Timur Dua Kota Palembang - Ramtika, Milsani; Waliah, Siti; Basron, Basron; Lusiana, Lusiana (Jurnal Publisitas, 2026)
This study aims to analyze the development of employee competence, particularly for Civil Servants (ASN), at the Ilir Timur Dua District Office in Palembang City to enhance performance and professionalism. Key performance indicators establish targets that must be achieved by every government agency to ensure the efficiency and effectiveness of administrative and operational tasks. Based on the 2023 E-SAKIP data, the Ilir Timur Dua District showed suboptimal performance indicators, specifically in community mutual cooperation (gotong royong) participation, the completion of government documents, and community involvement in religious activities. Additionally, this study examines the factors influencing these competencies. This research employs a descriptive qualitative method. The analysis of employee competence development is based on Sedarmayanti’s theory in Bryan Rafael (2023:5-9), utilizing four variables: technical competence, managerial competence, social competence, and intellectual/strategic competence. Meanwhile, the factors influencing competence development are analyzed based on Spencer & Spencer’s theory in Edy Sutrisno (2019:206), covering five variables: knowledge, skills, traits/attitudes, motives, and self-concept. The results indicate that competence development has not been optimally or evenly implemented, particularly in technical and managerial aspects. Conversely, supporting factors such as knowledge, skills, and attitudes are generally well-developed but still require strengthening in terms of organizational support and the equitable distribution of development programs.This study aims to analyze the development of employee competence, particularly for Civil Servants (ASN), at the Ilir Timur Dua District Office in Palembang City to enhance performance and professionalism. Key performance indicators establish targets that must be achieved by every government agency to ensure the efficiency and effectiveness of administrative and operational tasks. Based on the 2023 E-SAKIP data, the Ilir Timur Dua District showed suboptimal performance indicators, specifically in community mutual cooperation (gotong royong) participation, the completion of government documents, and community involvement in religious activities. Additionally, this study examines the factors influencing these competencies. This research employs a descriptive qualitative method. The analysis of employee competence development is based on Sedarmayanti’s theory in Bryan Rafael (2023:5-9), utilizing four variables: technical competence, managerial competence, social competence, and intellectual/strategic competence. Meanwhile, the factors influencing competence development are analyzed based on Spencer & Spencer’s theory in Edy Sutrisno (2019:206), covering five variables: knowledge, skills, traits/attitudes, motives, and self-concept. The results indicate that competence development has not been optimally or evenly implemented, particularly in technical and managerial aspects. Conversely, supporting factors such as knowledge, skills, and attitudes are generally well-developed but still require strengthening in terms of organizational support and the equitable distribution of development programs.